2013
DOI: 10.1039/c3cc41107a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed ortho-alkenylation of aryl hydrogen phosphates using a new mono-phosphoric acid directing group

Abstract: A highly efficient Pd-catalyzed ortho-alkenylation is reported using a mono-phosphoric acid-directing group for the first time. This phosphoric acid-directing group is successfully utilized for the synthesis of various alkenylated products and offers a new approach to transition-metal-catalyzed C-H activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 76 publications
(1 reference statement)
0
20
0
Order By: Relevance
“…In 2013, Kim, Lee, and co‐workers reported the highly efficient Pd II ‐catalyzed ortho ‐alkenylation and acetoxylation of phenols with olefins and [bis(acetoxy)iodo]benzene [PhI(OAc) 2 ] directed by a monophosphoric acid group (Scheme ). Both methods provided excellent regioselectivity and functional group tolerance.…”
Section: Ortho‐c−h Activation Of Phenolsmentioning
confidence: 99%
“…In 2013, Kim, Lee, and co‐workers reported the highly efficient Pd II ‐catalyzed ortho ‐alkenylation and acetoxylation of phenols with olefins and [bis(acetoxy)iodo]benzene [PhI(OAc) 2 ] directed by a monophosphoric acid group (Scheme ). Both methods provided excellent regioselectivity and functional group tolerance.…”
Section: Ortho‐c−h Activation Of Phenolsmentioning
confidence: 99%
“…31 Subsequently, phosphoric acid was used as a directing group by Kim, Lee, and co-workers [Scheme 12 (b)]. 32 The effectiveness of this directing group was utilized in phenol substrates giving products such as 28 and the scope of the reaction was demonstrated with different olefin partners. In 2013, Yang and co-workers reported the palladium-catalyzed C-H olefination of biaryls with phosphine oxide as the directing group to give products such as 29 [Scheme 12 (c)].…”
Section: Scheme 11 Hydroxyl-group-directed Ortho-c-h Bond Alkenylationmentioning
confidence: 99%
“…Encouraged by the developments of Pd-catalyzed diverse carbon-carbon and carbon-heteroatom bond forming reactions via the direct C−H activation [14,15], our co-authors including Cui and Wu et al reported a direct C-H functionalization of quinoline N-oxide(A, Scheme 2) with dimethyl H-phosphonate (B1, Scheme 2) to generate heteroaryl phosphonate [16] (G, Scheme 2) under metal-and external oxidant-free conditions. In this reaction, not only high efficiency can be obtained, but also practicality, environmental friendliness and atom economy can be featured.…”
Section: Introductionmentioning
confidence: 99%